(untitled) (Progressive Agriculture, 2021)
The study was conducted in the six major rice growing upazilas under the district of Mymensingh of Bangladesh during the period from January to December 2018. The purpose of the study was to find out the present status of rice residue management practices focusing on the environmental pollution and soil health. The data were collected from randomly selected 300 respondents with the help of pre-designed respective questionnaire to serve the objectives of the study. The results indicated that most of the respondents were illiterate and they have lack of knowledge on environmental pollution and soil health. About 54.33% of the respondents (163) managed their rice residues by incorporation, about 2.3% of respondent (7) open burning and 43.33% of the respondents (130) collected for other use as cattle feeding, cooking fuel, animal bedding, roofs of house making etc. There was a good sign for the environment as a few number of respondents used their rice residues as burning. About 33.66% of the respondents (95) reported that burning is harmful for environment, create breathing problems, 48.33% of the respondents (145) have no idea about this and 9.33% of the respondents (28) said burning produce toxic gas. About 47.66% of the respondents (143) had given opinion to increase soil fertility, 15% of the respondents (45) said increases soil productivity, 13.3% of the respondents (41) said reduce chemical fertilizer using and 9% of the respondents (27) said decrease soil erosion. Some of the respondents said that, rice residue incorporation in soil saves money (5.66%), easy to apply (18.66%), eco-friendly (3.66) and have no idea about it (72%). About 55% respondents were satisfied in existing residues management system whereas 45% have given negative responses. Management of rice residues have faced the problem as lack of available labors (48%), costly (9%), lack of storing place (25.66%), lack of modern technology (12.66%). Most (70.66%) of the respondents (212) were collected information of residue management and environment pollution by the television and radio programmes. Finally, it can be said that, with the highest production of rice in our country, a huge number of residues are also produced. Rice residues may cause environmental pollutions and soil health degradation. Proper management is needed to overcome this environmental pollution as well as soil health degradation through enhancing suitable and environment friendly residue management practices. Progressive Agriculture 31 (3): 178-189, 2020